Approach to Gender Transformation in Climate Change - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
The framework has been used to assess the gender transformative potential of 6 IDRC climate change projects, and make some changes in objectives, strategies and indicators. The activity is in year one of a 2-3 year project cycle.